Investigating the Alignment of the Lebanese National Mathematics Tests with the Curriculum Foundations at the Secondary Level - Itani, Dima (2022)
The aim of the present paper is to investigate the alignment of the Lebanese mathematics national tests with the foundations of the 1997 reformed curriculum, for the “Literature and Humanities” (LH) and “Life Sciences” (LS) tracks of the secondary level. Qualitative and quantitative content analysis techniques were used. Different components of the curriculum foundations were analyzed qualitatively as well as the structure and content of ten model tests issued by MEHE and ECRD as annexes to the curriculum, and 16 national tests for each track. The model and the national tests were quantitatively analyzed using an analysis framework that crossed their respective cognitive domains and content objectives. The cognitive domains are those of the TIMSS international assessments. Correlations were calculated and interpreted, considering the math content domains and the cognitive domains and taking into account the existence of different model tests issued at different time periods, between different sets of the model and national tests for each track, specifically between: 1) all the tests items of each of the national tests and the model tests, 2) the test items of the national tests of the years 2011-2013, 2015-2016, 2017-2018, and 2019, and between each of them and the test items of their corresponding model tests, and 3) the test items of the two sessions (session 1 and session 2) of the national tests. The quantitative analysis showed an overall high correlation between the national tests and the model tests for each track (r=0.97 at each track). However, the qualitative analysis and the results of correlations of the remaining sets showed a notable high correspondence between the model tests issued in the recent years and the national tests previously administered, signifying that a tradition of past tests has developed in the national examination setting and eventually defined the curriculum. Results also revealed a steady structure of the national tests emphasizing the “knowing” and “applying” cognitive domains and overlooking the “reasoning” domain, which reflects weak alignment with the curriculum foundation.